Analysis of Integrated Battery Energy Storage System with 1 MW Solar Power Plant - Amalia, Rif'ah; Sholihah, Fifi Hesty; Daffa, Halim Achmad (Journal of Research and Technology, 2023)
The research aims to evaluate the efficiency of BESS and provide recommendations for its improvement. Efficiency calculations involve comparing the input and output energy of BESS, utilizing data retrieved from the Rapid SCADA system in the Control Room (CR) of PLTS. The main findings of this study indicate an overall BESS efficiency of 62.95% and a specific efficiency of 50% for the year 2023. The observed lower efficiency is attributed to a charging system employing excessively high voltages. This overvoltage charging also contributes to an estimated 17% increase in BESS battery degradation.